2012
DOI: 10.1152/ajpregu.00077.2012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of protein degradation in mantle muscle and proposed gill remodeling in starvedSepia officinalis

Abstract: -Cephalopods have relatively high rates of protein synthesis compared to rates of protein degradation, along with minimal carbohydrate and lipid reserves. During food deprivation on board protein is catabolized as a metabolic fuel. The aim of the current study was to assess whether biochemical indices of protein synthesis and proteolytic mechanisms were altered in cuttlefish, Sepia officinalis, starved for 7 days. In mantle muscle, food deprivation is associated with a decrease in protein synthesis, as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 38 publications
12
36
0
Order By: Relevance
“…Cathepsin A-, B-, H-, and L-like proteases were elevated, as were indices of the ubiquitin-proteasome pathway. Most notably, there were increases in proteasome (␤-subunit) and polyubiquitin transcript levels, and polyubiquinated protein (21). These biochemical indices imply that protein synthesis is curtailed during the early stages of food deprivation in the mantle of S. officinalis, and as starvation ensues, mantle protein is catabolized.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Cathepsin A-, B-, H-, and L-like proteases were elevated, as were indices of the ubiquitin-proteasome pathway. Most notably, there were increases in proteasome (␤-subunit) and polyubiquitin transcript levels, and polyubiquinated protein (21). These biochemical indices imply that protein synthesis is curtailed during the early stages of food deprivation in the mantle of S. officinalis, and as starvation ensues, mantle protein is catabolized.…”
mentioning
confidence: 95%
“…We have previously shown that in the mantle of fooddeprived cuttlefish, at a time when digestive gland triglycerides were being mobilized, total RNA levels were decreased and cellular signaling pathways stimulating protein synthesis were disengaged (21). More specifically, the phosphorylation of AKT and 4EBP1 decreased.…”
mentioning
confidence: 99%
See 3 more Smart Citations